Quality of life among infertile PCOS patients - YOLDEMİR, AHMET TEVFİK (SPRINGER HEIDELBERG, 2019)
ObjectiveTo investigate whether quality of life differs between PCOS and non-PCOS infertile women.Study designTwo questionnaire forms of quality of life (PCOSQ, SF-36) were given to 238 women. Patients were asked to answer all of the questions in both of the questionnaires. Of these 238 women, only 49 infertile PCOS patients, 47 infertile non-PCOS patients and 62 fertile PCOS patients flled the forms completely.ResultsBoth PCOSQ and SF-36 scores are lowest in infertile PCOS group. Although total PCOSQ score of infertile non-PCOS group was better than non-infertile PCOS and fertile PCOS groups; there was trend for lower scores when infertility is added on PCOS status.ConclusionThe quality of life is lowest among infertile PCOS women. Both PCOS and infertility as individual factors may have negative impact in quality of life of reproductive age women.
Keywords: PCOS; Quality of life; Infertility; PCOSQ; POLYCYSTIC-OVARY-SYNDROME; QUESTIONNAIRE PCOSQ; WOMEN; DIAGNOSIS; CONSENSUS; CRITERIA